Pengembangan Sistem Informasi Layanan Antrian Digital pada UPT Puskesmas Durian Luncuk - Jayanto, Anthony; Fachruddin, Fachruddin (LPPM Universitas Dinamika Bangsa, 2024)
The queue service information system was researched and developed at the Unit Pelayanan Terpadu (UPT) of the Puskesmas Durian Luncuk with the aim of improving the efficiency and convenience of patient services. This research employed an approach that involved problem identification, literature review, observation, interviews, and the analysis of primary and secondary data documents. In the existing queue service system, it only functions as a patient queue management tool. Consequently, using this manual system presents numerous challenges in providing interactive information for patients, administrators, and management. Based on these findings, the researcher developed a Digital Queue Service Information System at the Puskesmas Durian Luncuk, employing a First-In-First-Out (FIFO) queue model and a single-server model (M/M/1). The system development methodology used the waterfall model, and it was designed using Unified Modeling Language (UML). In the development phase, the author utilized the Python language and MySQL Server. This research contributes to the enhancement of healthcare service management and strengthens the implementation of information technology in the healthcare sector.